Localization and sequence analysis of chloroplast DNA sequences of Chlamydomonas reinhardii that promote autonomous replication in yeast - Vallet, J.-M. (1984)
Four distinct chloroplast DNA segments from Chlamydomonas reinhardii of 400, 415, 730 and 2300 bp which promote autonomous replication in yeast have been mapped on the chloroplast genome. Plasmids carrying these chloroplast DNA fragments are unstable in yeast when the cells are grown under non-selective conditions. Sequence analysis of three of these chloroplast ARS regions (autonomously replicating sequences in yeast) reveals a high AT content, numerous short direct and inverted repeats and the presence of at least one element in each region that is related to the yeast ARS consensus sequence. A/T TTTATPuTTT A/T. These three chloroplast regions share, in addition, two common elements of 10 and 11 bp which may play a role in promoting autonomous replication.